Optimum design of truss structures undergoing large deflections subject to a system stability constraint - Sedaghati, R.; Tabarrok, B. (International journal for numerical methods in engineering, 2000)
A structural optimization algorithm is developed for shallow trusses undergoing large deflections subject to a system stability constraint. The method combines the non‐linear buckling analysis, through displacement control technique, with the optimality criteria approach. Four examples illustrate the procedure and allow the results obtained to be compared with those in the literature. It is shown that a design based on the generalized eigenvalue problem (linear buckling) highly underestimates the optimum mass for these types of structures so a design based on the linear buckling analysis can result in catastrophic failure. In one of the design examples the stresses in the elements, in the optimum design, exceed the allowable stresses, pointing out the need for a design that accounts for both non‐linear buckling and stress constraints. Copyright © 2000 John Wiley & Sons, Ltd.